From smart specialisation to smart experimentation: building a new theoretical framework for regional policy of the European Union - Benner, Maximilian (Zeitschrift für Wirtschaftsgeographie, 2014)
Abstract: The idea of smart specialisation has gained high prominence in the discourse about the regional policy of the European Union (EU). In the coming program period from 2014 to 2020 it is expected to be a major pillar of EU structural funds. The notion of smart specialisation incorporates some basic principles of evolutionary economics and centers on the idea of an entrepreneurial discovery process of new trajectories on the regional level. It does not, however, sufficiently take into account the relevance of individual agents, their actions, and their relations with each other in the identification, creation, development, and destruction of technological and economic trajectories. For this, a focus on micro-level dynamics is needed that provides the base for experimentation. Therefore, this paper proposes the new concept of smart experimentation. This notion aims to complement smart specialisation. It is anchored not only in evolutionary economics, but also in relational economic geography.
Online veröffentlicht: 21.10.2015
Gesehen am 09.10.2020